EVALUATION OF THE APPLICATION OF BLOOM'S TAXONOMY IN ISLAMIC RELIGIOUS EDUCATION LEARNING - Pangestu, Riyas Agung; Anshori, Ari (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
Education is the most important thing in human life entitled to get and expected to always develop in it, education has the meaning of a life process in developing each individual to be able to live and live life. Man is educated to be a good useful person. The first education obtained by each is the family environment, school environment, and community environment This research was designed using a qualitative approach because the expected results were not in the form of numerical data. Selection of qualitative approach in the preparation of research This research also uses a type / research approach in the form of literature studies Cognitive aspects refer to the processes of thought, knowledge, and understanding involved in learning and other intellectual activities Evaluation of cognitive aspects can be done through written tests, exams, project assignments, and presentations